One-hour social and reproductive behavioral time series of Japanese quail in diverse social environments - Alcala, Rocio Soledad (2022)
Social groups composed of three adult quail, 2 females and 1 male (156-171 days old). We evaluated social and reproductive behavior in these groups. Groups were housed in a white wooden apparatus measuring 80 x 40 x 40 cm (width x length x height, respectively) with wood-shavings on the floor. A feeder and an automatic nipple drinker were positioned in opposite corners of the apparatus. Nylon monofilament line was extended over the top of the boxes with a 1 cm separation in order to prevent the birds from escaping without interfering with their visualization. A video camera was suspended 1.5m above the box. Since only 4 social groups could be tested simultaneously, the setup was repeated 3 consecutive times. For convenience boxes in which each social group were placed were numbered 1-12, where boxes 1-4 were tested simultaneously first, 5-8 second and 9-12 last. We used the ANY-MAZE@ to register the following behaviors as described in Caliva et al. (2017) during a one-hour period between 9 and 10 am inmediatly after placing in box (Day1) after 48h of habituation to the novel setting (Day3): Pecks: when one bird raises its head and vigorously pecks the other bird?s body (usually on the head). Grabs: when a male catches (?grabs?) with their beak the neck or head region of the female. Mounts: while performing a grab, the male approaches a female from behind, and places both feet on the dorsal surface of its torso, stepping over the females? tail. Cloacal contacts: during mounting, the male lifts his tail and tilts his pelvis underneath the other bird and briefly presses its cloaca against the female. Threats: one bird stands with its neck and head raised in front of the other bird that usually has its head at a lower level than the first. Chase: a bird runs after another that is escaping. Foraging: pecking at the ground or actively moving litter with beak. Feeding: peaking at food in the feeding trough. Dust bathing: vertical wing shakes in a lying position . Time series denote with the number one changes towards actively performing the given behavior, while the number zero indicates cessation of that behavior. All time series are stored as text files (.txt). Considering that the 36 animals were evaluated in 12 mixed-sex groups of 3 birds in individual experimental boxes, each subject quail was identified by their experimental group number (Box), ID number of wing band, and sex (femaleA, femaleB or male). In the case of females an indication A or B is used to discriminate between the two. In the file name an indication of the corresponding bird is provided as "BoxNº_IDNº_sex_DayNº" Data descriptor submitted to Sci Data "High resolution behavioral time series of Japanese quail within their their social environment"